Removal of Phenolics from Wastewater by Fe2O3 Impregnated Sawdust as Adsorbent: Adsorption Isotherm and Kinetic Studies - Nayak, Arunima; Bhushan, Brij; Gupta, Vartika (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983548);" role="presentation">In this study, <span dir="ltr" style="left: calc(var(–scale-factor)*130.22px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948355);" role="presentation">magnetic nanoparticles (MNPSD) from abundantly available lignocellulosic waste viz. sawdust <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875648);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909924);" role="presentation">successfully <span dir="ltr" style="left: calc(var(–scale-factor)*145.46px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950844);" role="presentation">synthesized via co-<span dir="ltr" style="left: calc(var(–scale-factor)*226.25px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948038);" role="presentation">precipitation method <span dir="ltr" style="left: calc(var(–scale-factor)*316.15px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921733);" role="presentation">and consequently used <span dir="ltr" style="left: calc(var(–scale-factor)*415.42px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01206);" role="presentation">for the removal of <span dir="ltr" style="left: calc(var(–scale-factor)*498.58px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918905);" role="presentation">model <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911951);" role="presentation">phenolics (Catechol and Resorcinol) from aqueous solution under batch mode method. Batch adsorption studies <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960951);" role="presentation">revealed irrespective of adsorbate types, higher sorption of <span dir="ltr" style="left: calc(var(–scale-factor)*325.87px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984686);" role="presentation">such phenolics occurring at acidic pH (pH=3), <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922845);" role="presentation">contact time of 60mins and at 25ºC. The results obtained from pH studies indicates <span dir="ltr" style="left: calc(var(–scale-factor)*411.67px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921918);" role="presentation">that electrostatic interaction <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960162);" role="presentation">may be responsible for the binding of Catechol and Resorcinol onto MNPSD, while film or particle <span dir="ltr" style="left: calc(var(–scale-factor)*487.54px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97253);" role="presentation">diffusion <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893721);" role="presentation">mechanisms <span dir="ltr" style="left: calc(var(–scale-factor)*124.10px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921244);" role="presentation">to be operative during the transfer of such phenolics from the <span dir="ltr" style="left: calc(var(–scale-factor)*374.83px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99857);" role="presentation">liquid <span dir="ltr" style="left: calc(var(–scale-factor)*400.87px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897288);" role="presentation">phase. The isotherm <span dir="ltr" style="left: calc(var(–scale-factor)*485.14px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900336);" role="presentation">outcomes <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880574);" role="presentation">demonstrated <span dir="ltr" style="left: calc(var(–scale-factor)*129.74px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946807);" role="presentation">that irrespective of adsorbate types, Langmuir model <span dir="ltr" style="left: calc(var(–scale-factor)*353.83px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941488);" role="presentation">was operative over the studied phenolics <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924444);" role="presentation">concentration and <span dir="ltr" style="left: calc(var(–scale-factor)*150.02px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933019);" role="presentation">kinetics d<span dir="ltr" style="left: calc(var(–scale-factor)*190.73px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970894);" role="presentation">ata followed <span dir="ltr" style="left: calc(var(–scale-factor)*247.01px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864338);" role="presentation">pseudo-<span dir="ltr" style="left: calc(var(–scale-factor)*278.69px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.860802);" role="presentation">second-<span dir="ltr" style="left: calc(var(–scale-factor)*309.91px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951034);" role="presentation">order model <span dir="ltr" style="left: calc(var(–scale-factor)*365.11px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986173);" role="presentation">over the entire time frame<span dir="ltr" style="left: calc(var(–scale-factor)*477.22px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982669);" role="presentation">. Thus, the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900409);" role="presentation">experimental results reveal the <span dir="ltr" style="left: calc(var(–scale-factor)*196.97px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87218);" role="presentation">usefulness <span dir="ltr" style="left: calc(var(–scale-factor)*241.01px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960852);" role="presentation">of MNPSD <span dir="ltr" style="left: calc(var(–scale-factor)*288.77px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87455);" role="presentation">as a suitable <span dir="ltr" style="left: calc(var(–scale-factor)*340.27px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904808);" role="presentation">Nano <span dir="ltr" style="left: calc(var(–scale-factor)*364.39px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896453);" role="presentation">adsorbent for wastewater <span dir="ltr" style="left: calc(var(–scale-factor)*467.38px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897323);" role="presentation">treatment.